NYX‐2925 induces metabotropic N‐methyl‐d‐aspartate receptor (NMDAR) signaling that enhances synaptic NMDAR and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor. Issue 5 (16th October 2019) - Bowers, M. Scott; Cacheaux, Luisa P.; Sahu, Srishti U.; Schmidt, Mary E.; Sennello, Joseph A.; Leaderbrand, Katherine; Khan, M. Amin; Kroes, Roger A.; Moskal, Joseph R.
Abstract: N ‐methyl‐d ‐aspartate receptors (NMDARs) mediate both physiological and pathophysiological processes, although selective ligands lack broad clinical utility. NMDARs are composed of multiple subunits, but N ‐methyl‐d ‐aspartate receptor subunit 2 (GluN2) is predominately responsible for functional heterogeneity. Specifically, the GluN2A‐ and GluN2B‐containing subtypes are enriched in adult hippocampus and cortex and impact neuronal communication via dynamic trafficking into and out of the synapse. We sought to understand if ((2S, 3R)‐3‐hydroxy‐2‐((R)‐5‐isobutyryl‐1‐oxo‐2, 5‐diazaspiro[3, 4]octan‐2‐yl) butanamide (NYX‐2925), a novel NMDAR modulator, alters synaptic levels of GluN2A‐ or GluN2B‐containing NMDARs. Low‐picomolar NYX‐2925 increased GluN2B colocalization with the excitatory post‐synaptic marker post‐synaptic density protein 95 (PSD‐95) in rat primary hippocampal neurons within 30 min. Twenty‐four hours following oral administration, 1 mg/kg NYX‐2925 increased GluN2B in PSD‐95‐associated complexes ex vivo, and low‐picomolar NYX‐2925 regulated numerous trafficking pathways in vitro . Because the NYX‐2925 concentration that increases synaptic GluN2B was markedly below that which enhances long‐term potentiation (mid‐nanomolar), we sought to elucidate the basis of this effect. Although NMDAR‐dependent, NYX‐2925‐mediated colocalization of GluN2B with PSD‐95 occurred independent of ion flux, as colocalization increased in the presence of either the NMDAR channel blocker (5R, 10S)‐(–)‐5‐Methyl‐10, 11‐dihydro‐5H‐dibenzo[a, d]cyclohepten‐5, 10‐imine hydrogen maleate or glycine site antagonist 7‐chlorokynurenic acid. Moreover, while mid‐nanomolar NYX‐2925 concentrations, which do not increase synaptic GluN2B, enhanced calcium transients, functional plasticity was only enhanced by picomolar NYX‐2925. Thus, NYX‐2925 concentrations that increase synaptic GluN2B facilitated the chemical long‐term potentiation induced insertion of synaptic α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor GluA1 subunit levels. Basal (unstimulated by chemical long‐term potentiation) levels of synaptic GluA1 were only increased by mid‐nanomolar NYX‐2925. These data suggest that NYX‐2925 facilitates homeostatic plasticity by initially increasing synaptic GluN2B via metabotropic‐like NMDAR signaling. Cover Image for this issue: doi: 10.1111/jnc.14735 . Abstract : ((2S, 3R)‐3‐hydroxy‐2‐((R)‐5‐isobutyryl‐1‐oxo‐2, 5‐diazaspiro[3, 4]octan‐2‐yl) butanamide (NYX‐2925) is a novel N ‐methyl‐d ‐aspartate (NMDA) modulator that enhances LTP. Here, we sought to determine its mechanism of action. (a) NYX‐2925 engages homeostatic plasticity by exhibiting dose‐dependent mechanism of action at NMDARs (multi‐subunit calcium channels). (b, b′) low picomolar NYX‐2925 increases synaptic post‐synaptic density protein 95 (PSD‐95)‐colocalized N ‐methyl‐d ‐aspartate receptor subunit 2, subtype B (GluN2B)‐containing NMDA receptors (within 30 min). (c, c′) Mid‐nanomolar concentrations flux calcium and decrease synaptic GluN2B after 60 min. In contrast to mid‐nanomolar, the low‐picomolar mechanism appears metabotropic (ion flux independent). Synaptic GluA1 is increased by NYX‐2925 concentrations that mediate ion flux and/or chemical long‐term potentiation, which is further increased by metabotropic‐like NYX‐2925 concentrations. NYX‐2925 is a powerful tool to interrogate both canonical and unconventional modes of signaling through the NMDA receptor. Cover Image for this issue: doi: 10.1111/jnc.14735 .